Respon Pertumbuhan Tanaman Kacang Hijau (Vigna radiata) dalam Kondisi Cekaman Kekeringan dengan Pemberian Air Kelapa - Noviana, Kharisma Yosi; Anugrah, Devi (IAIN Ternate, 2024)
Imports of green beans in various countries have increased rapidly. One of China's largest suppliers of green beans is Indonesia, namely around 25,774 tonnes in 2020. But foreign imports are not comparable to green bean production. This is due to erratic climate changes causing plants to suffer from drought. This research aims to determine the growth response of green bean plants (Vigna radiata) under drought stress by providing coconut (Cocos nucifera) water. This research uses quantitative experimental methods. Sampling used a Completely Randomized Design (CRD) using 5 stress treatments (water content 100%, 75%, 50%, 25%, and 0% soil field capacity + 40% concentration of coconut water) and each treatment was repeated 5 times. So we obtained 15 sample units of green bean plants (Vigna radiata). The research results were analyzed using ANOVA with the DMRT follow-up test, showing that coconut water had no effect on plant height and plant root length. But it has a real effect on the number of leaves of green bean plants. On average, the highest number of leaves found at P0 (100% water content of soil field capacity + 40% concentration of coconut water) is around 5 pieces. Meanwhile, the average number of smallest leaves is at P4 (0% water content + soil field capacity + 40% coconut water concentration) around 1.80 pieces.